THE INFLUENCE OF KNOWLEDGE, PROMOTION, AND SOCIAL ENVIRONMENT ON THE INTEREST OF MUSLIM STUDENTS IN MALANG CITY TO BECOME CUSTOMERS OF BANK SYARIAH INDONESIA WITH RELIGIOSITY AS A MODERATING VARIABLE - Akbar, Muhd Syahrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze (1). The effect of knowledge, promotion, and the social environment on the interest of Muslim students in Malang City to become Bank Syariah Indonesia (BSI). Customers. (2). The influence of religiosity can moderate the effect of knowledge, promotion, and social environment on the interest of Muslim students in Malang City who want to become BSI customers. This study uses quantitative methods with data collection techniques using questionnaires. The population in this study were Muslim students in Malang City. The sampling technique used purposive sampling, so the number of participants in this study was 164. Data analysis techniques in this study used Moderated Regression Analysis with the help of IBM SPSS Statistics 26 Software. The study results showed that knowledge and the social environment based on partial variables positively and significantly affect Muslim students' interest in saving to become BSI customers in Malang City. In contrast, the promotion variable does not positively affect Muslim students' interest in becoming BSI customers in Malang City. Moreover, religiosity can moderate the effect of the knowledge variable on the interest of Muslim students in Malang City in becoming BSI customers. However, religiosity cannot moderate the influence of promotion and social environment variables on the interest of Muslim students in Malang City in becoming BSI customers.